2022
DOI: 10.1007/s42979-022-01016-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Instructional Strategies Designed for Older Adults in Learning Digital Technologies: A Systematic Literature Review

Abstract: An ageing population is a universal phenomenon experienced worldwide. In parallel with these demographic changes, a significant breakthrough in digital devices has also influenced this digital age. Designing instructional strategies to promote meaningful learning among older adult learners has been a long-standing challenge. To enhance older adults’ life-long learning experiences, implementing instructional strategies in the process through which such adults learn can help to improve effective learning. Despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Older adults value CL with and from their peers about important health issues such as diabetes and cancer [25]. Within the context of learning to use computers, CL has been found to be effective for both learning outcomes and social development in older adults [26][27][28], although an earlier study [29] found that older adults performed similarly in computer learning regardless of learning individually or in pairs. In the context of eHealth literacy, CL enables opportunities to learn new health information and skills to access such information on the web [21].…”
Section: Collaborative Learning In Community Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Older adults value CL with and from their peers about important health issues such as diabetes and cancer [25]. Within the context of learning to use computers, CL has been found to be effective for both learning outcomes and social development in older adults [26][27][28], although an earlier study [29] found that older adults performed similarly in computer learning regardless of learning individually or in pairs. In the context of eHealth literacy, CL enables opportunities to learn new health information and skills to access such information on the web [21].…”
Section: Collaborative Learning In Community Settingsmentioning
confidence: 99%
“…In the context of eHealth literacy, CL enables opportunities to learn new health information and skills to access such information on the web [21]. Similarly, Ahmad et al [26] have suggested that CL allows older adult learners to participate with peers and interact effectively to learn digital technology.…”
Section: Collaborative Learning In Community Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In research by Pappas et al (2019), the utilization of videos that serves as an explanation outlet, among with graphics in modules, handbooks, or even manuals is essential for elderly learning, as it is also one of the preferred learning material by the elderly learners. Other researchers also highlighted that using explanatory videos in the learning process of elders enhances the effectiveness of the lesson, as it could help sustain the elders' attention and helps maintain their focus on learning digital technologies (Hansen et al, 2019;Smith et al, 2019;Ahmad et al, 2022). P1: "in order for us to create a program with the intent of giving exposure of technology for the elders, the instructions that will be given should not be complicated.…”
Section: Incorporate Audio-visual Aidsmentioning
confidence: 99%
“…The use of digital health technologies during a crisis enables the government to quickly respond to and effectively contain the epidemic. But the widespread use of digital health technologies during the COVID-19 epidemic without taking into account the age-related digital divide has led to a number of problems [10]. It was regularly reported that older adults were unable to get medical care, board public transportation, or engage in commercial transactions because they lacked the necessary digital codes [11].…”
Section: Introductionmentioning
confidence: 99%